2022
DOI: 10.3390/medicina58020283
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Recovery from COVID-19-Induced Smell Loss and General and Oral Health Factors

Abstract: Background and Objectives: Loss of smell is one of the strongest predictors of coronavirus disease 2019 (COVID-19) and can persist long after other symptoms have resolved. “Long” cases (>28 days) of smell dysfunction present future challenges to medical and dental professionals, as there is a lack of evidence on the causes and any exacerbating or relieving factors. This study aimed to explore the persistence of COVID-19-induced smell loss and association with physical, lifestyle and oral health factors. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Given the close relationship between taste and smell recovery that we observe, it is unsurprising that the associated differences between prolonged (>28 day) and rapid (≤28 day) taste recovery are in line with our previous work on smell recovery [25]. The main difference was that illness severity was not significantly associated with recovery, although the relationship approached significance with p = 0.06.…”
Section: Differences Between Prolonged and Rapid Taste Recoverysupporting
confidence: 86%
See 3 more Smart Citations
“…Given the close relationship between taste and smell recovery that we observe, it is unsurprising that the associated differences between prolonged (>28 day) and rapid (≤28 day) taste recovery are in line with our previous work on smell recovery [25]. The main difference was that illness severity was not significantly associated with recovery, although the relationship approached significance with p = 0.06.…”
Section: Differences Between Prolonged and Rapid Taste Recoverysupporting
confidence: 86%
“…Firstly, as it was conducted during the first wave of global lockdowns, mass testing was not readily available and thus participants with symptomatic diagnoses without PCR confirmation were included. Given the roughly equivalent specificity of sensory symptoms to PCR test and our analyses of individuals displaying sensory symptoms, this did not have much bearing on results when comparing PCR positive participants only [25]. A major challenge in the study of taste disorders in COVID-19 is the reliance of self-reported data rather than objective tests.…”
Section: Limitations and Future Workmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies on adults found that anosmia affected more young adults (between 20–40 years of age) in comparison with older adults, tending also to be associated with a longer persistence of anosmia itself in the post-acute phase [ 14 , 42 , 48 ].…”
Section: Discussionmentioning
confidence: 99%